Makna Interaksi Parasosial Penggemar K-Pop dalam Berkomunikasi di Microblog - Mirsya Hanifa Suryadi; Firmansyah (UNISBA Press, 2024)
Abstract. Indonesia has become one of the countries with the most fans of Korean music and culture in the world, especially K-pop fans. In this case, fans have a very important role in the spread of Korean culture, especially k-pop. This study aims to determine the meaning of parasocial interactions carried out by fans with K-pop idols on microblogs. Parasocial interaction is a form of interaction in which a person interacts with their idol as if the idol is a real figure they support. This research uses qualitative research methods and phenomenological approaches using Alfred Schutz's phenomenological theory, and the data collection techniques used are literature review and in-depth interviews with semi-structured techniques, as well as data verification techniques through triangulation analysis. This research focuses on knowing the meaning of Stray Kids fan interactions on Twitter or X. The results showed that parasocial interactions provide deep meanings for fans, including as encouragement, support systems, friends, and significant others, giving the illusion of dating, being a benchmark, handle, and reason to survive, life goals, new life,